Social and Cultural Factors Leading to Suicide Attempt via Organophosphate Poisoning in Nepal - Licata, Christine; Liu, Lawrence; Mole, Dale; Thorp, Jonathon; Chand, Rajesh; Chaulagain, Sabin (Case Reports in Psychiatry, 2019)
Organophosphates are commonly used in rural, agricultural communities worldwide. Poisoning in Nepal is commonly a result of suicide attempt via ingestion with a mortality rate of 41 times higher than in the United States even after appropriate treatment. The patient discussed in this case is a 46-year-old Nepalese female with a complicated psychosocial history that presented with a suicide attempt via organophosphate ingestion. She required higher doses and greater lengths of treatment of atropine and pralidoxime to resolve symptoms of toxicity that resulted in atropine-induced psychosis, a side effect rarely cited in the literature. This patient was one of many who attempt suicide in Nepal, where suicide is the leading cause of death for young to middle aged women in the country.